2004
DOI: 10.1124/jpet.104.078212
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin D2-Induced Eosinophilic Airway Inflammation Is Mediated by CRTH2 Receptor

Abstract: Mast cell-derived prostaglandin D 2 (PGD 2 ) is one of the essential modulators of eosinophilic airway inflammation in asthma and allergic rhinitis. Two G protein-coupled receptors for PGD 2 , prostaglandin D 2 receptor (DP) and chemoattractant receptorhomologous molecule expressed on Th 2 cells (CRTH2), are both expressed on the surface of eosinophils, and CRTH2 has been demonstrated to mediate PGD 2 -induced eosinophil mobilization in vitro. However, it has not yet been determined whether PGD 2 and its recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 26 publications
(54 reference statements)
5
48
2
Order By: Relevance
“…As we have previously reported (30), intratracheal instillation of PGD 2 in PBSexposed rats did not increase the number of eosinophils in BAL fluid. In contrast, PGD 2 , in a dose of 0.1-1 nM/animal, produced a significant increase in the number of eosinophils in BAL fluid of OVA-exposed animals (Fig.…”
Section: Figuresupporting
confidence: 72%
See 2 more Smart Citations
“…As we have previously reported (30), intratracheal instillation of PGD 2 in PBSexposed rats did not increase the number of eosinophils in BAL fluid. In contrast, PGD 2 , in a dose of 0.1-1 nM/animal, produced a significant increase in the number of eosinophils in BAL fluid of OVA-exposed animals (Fig.…”
Section: Figuresupporting
confidence: 72%
“…In a previous study, we found that intratracheal PGD 2 induced a marked influx of eosinophils into the airways of rats pretreated with i.v. IL-5, but not of untreated rats (30). In the experiments reported herein, we found that PGD 2 recruited eosinophils into the airspace of allergen-exposed animals; there were, however, several differences in the responses to PGD 2 between the IL-5-pretreatment and the OVAsensitization/exposure models.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Prostaglandin D 2 (PGD 2 ) is a well known inflammatory mediator in peripheral tissues (Matsuoka et al, 2000;Honda et al, 2003;Kabashima and Narumiya, 2003), invoking airway inflammation (Matsuoka et al, 2000;Shiraishi et al, 2005), inhibiting platelet aggregation (Yun et al, 1991), and causing peripheral vasodilatation (Soter et al, 1983;Alving et al, 1991). PGD 2 is synthesized by hematopoietic PGD synthase (HPGDS) and lipocalin-type PGDS (L-PGDS) and exerts its actions by binding to specific receptors, DP 1 or DP 2 (Kabashima and Narumiya, 2003;Nagata and Hirai, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, CRTH2 is predominantly expressed by Th2 cells, eosinophils, and basophils, all known to play a key role in allergic diseases. 1 Activation of the Gi-coupled CRTH2 by PGD 2 or the selective agonist DK-PGD 2 stimulates chemotaxis of human Th2 cells, eosinophils, and basophils in vitro and in vivo, 2,3 suggesting that the CRTH2 receptor may directly mediate the recruitment of inflammatory cells in allergic diseases such as asthma, allergic rhinitis, and atopic dermatitis. CRTH2 is expressed by antigen-specific Th2 cells in allergic individuals supporting this notion that the CRTH2 receptor is important in the recruitment of Th2 in allergic diseases in humans.…”
mentioning
confidence: 99%